2012
DOI: 10.1016/j.freeradbiomed.2011.10.490
|View full text |Cite
|
Sign up to set email alerts
|

8-Oxoguanine-DNA glycosylase 1 deficiency modifies allergic airway inflammation by regulating STAT6 and IL-4 in cells and in mice

Abstract: 8-oxoguanine-DNA glycosylase (OGG-1) is a base excision DNA repair enzyme; however, its function in modulating allergic diseases remains undefined. Using OGG-1 knockout (KO) mice, we show that this protein impacts allergic airway inflammation following sensitization and challenge by ovalbumin (OVA). OGG-1 KO mice exhibited less inflammatory cell infiltration and reduced oxidative stress in the lungs after OVA challenge compared to WT mice. The KO phenotype included decreased IL-4, IL-6, IL-10, and IL-17 in lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
66
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 61 publications
(78 reference statements)
9
66
1
Order By: Relevance
“…Furthermore, we found a higher frequency (Fig. 6B, compare Increased Susceptibility of Neil2-null Mice to InflammationPrevious reports have indicated that Ogg1-null mice have decreased susceptibility to LPS-induced and oxidative stressinduced inflammation (44,45) and also to allergic immune responses (46,47). To address the susceptibility of Neil2-null mice to inflammation, animals were challenged intranasally with LPS (100 ng/per lung) or TNF-␣ (20 ng/lung) or GOx (1 milliunit/lung).…”
Section: Neil2 Is Required For Maintaining Telomere Length Homeostasisupporting
confidence: 49%
“…Furthermore, we found a higher frequency (Fig. 6B, compare Increased Susceptibility of Neil2-null Mice to InflammationPrevious reports have indicated that Ogg1-null mice have decreased susceptibility to LPS-induced and oxidative stressinduced inflammation (44,45) and also to allergic immune responses (46,47). To address the susceptibility of Neil2-null mice to inflammation, animals were challenged intranasally with LPS (100 ng/per lung) or TNF-␣ (20 ng/lung) or GOx (1 milliunit/lung).…”
Section: Neil2 Is Required For Maintaining Telomere Length Homeostasisupporting
confidence: 49%
“…(42)(43)(44)(45)(46)(47). Allergic asthma, oxidative stress, and lung inflammation go hand-in-hand (48,49). There are reports suggesting that EC-SOD plays a major role in determining the progression of allergic lung disease by controlling DC maturation and T lymphocyte priming, differentiation, proliferation, and activation (25).…”
Section: Discussionmentioning
confidence: 99%
“…Mabley and colleagues showed that that Ogg 1-null mice are resistant to endotoxin (LPS)-induced organ dysfunction, neutrophil infiltration, and oxidative stress compared to the response seen in wild-type controls (12). In another study, sensitized Ogg 1-null mice exhibited lower IL-4, IL-6, IL-10, and IL-17 production and decreased levels of inflammatory cell infiltration and oxidative stress in the lungs after ovalbumin challenge compared to levels in wild-type controls (13). Bacsi and colleagues showed that supraphysiological levels of 8-oxoG in the genome of the airway epithelium (AE) due to decreased OGG1 expression evoked a lower inflammatory response in challenged-sensitized mice, as determined by expression of Th2 cytokines, eosinophilia, epithelial metaplasia, and airway hyperresponsiveness (AHR) (14).…”
Section: Introductionmentioning
confidence: 99%